Waste ceramic powder for sustainable concrete production as supplementary cementitious material - Özkılıç, Yasin Onuralp; Bahrami, Alireza; Güzel, Yusuf; Soğancı, Ali Sinan; Karalar, Memduh; Althaqafi, Essam; Çelik, Ali İhsan; Zeybek, Özer; Jagadesh, P. (Frontiers in Materials, 2025)
A detailed examination was carried out by substituting waste ceramic powder (WCP) at certain ratios in the cement mortar. To achieve this, five different WCP percentages (10%, 20%, 30%, 40%, and 50%) were used in the manufacturing of concrete. First, the workability and slump values in the fresh state of concrete were determined by performing a slump test. Subsequently, to assess the effectiveness of concrete fabricated using WCP, several tests, including compressive strength (CS), splitting tensile strength (STS), and flexural strength (FS), tests were conducted on the specimens. In light of the various numbers of waste materials utilized, variations in strength capacity were determined. The findings demonstrated that by including WCP at concentrations of 10%, 20%, 30%, 40%, and 50%, there was a corresponding reduction in CS of 5.8%, 21.8%, 47.1%, 63.2%, and 73.6%, respectively. The decreases in STS were 6.3%, 13.8%, 35.2%, 49.7%, and 65.4%, respectively, when a plain concrete STS value of 1.59 MPa was considered.Similarly, when the WCP content increased, FS was reduced by 15.3%, 21.4%, 31.6%, 44.9%, and 54.1%, respectively. This is very significant because it represents one of the key issues in calculating the optimal quantity of WCP in relation to both the strength and the amount of waste materials used. Furthermore, taking into account our experimental research and previous studies on concrete produced using WCP, straightforward equations were provided for practical use to predict CS, STS, and FS. On the other hand, scanning electron microscopy was conducted on validate the findings obtained from the experimental part of the study. The results also showed that WCP provided good cement adhesion. The artificial neural network modeling technique was adopted to estimate the concrete properties with coefficients of determination of 0.944 (CS), 0.900 (STS), and 0.856 (FS) with K-fold cross-validation.